Analisis Perbandingan Metode PD T-05-2005-B Dan Pedoman MDPJ No. 04/Se/DB/2017 Dalam Perencanaan Overlay Pada Ruas Jalan SM. Amin Pekanbaru - M. Nurul; Elianora Elianora; M. Yusa (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Road is a land transport infrastructure which has important role to facilitate economic activities in a certain area. SM. Amin Road in Pekanbaru is a causeway that connects Pekanbaru city to Minas, Siak. Any damage found on the road can cause serious inconvenience to road users, hence a essential maintenance deemed necessary. Improper overlay design may cause the rapid deterioration (under-design) or the overlay construction is uneconomical (over-design). Therefore, it’s required a spesific method to get a good design overlay. This study revealed that overlay is required for SM. Amin road at KM 03+900 – 05+200. This study compared two different methods of overlay design i.e. Pd T-05-2005-B and i.e. No.04/SE/DB/2017. Pd T-05-2005-B gives overlay thickness of 20 cm where as No.04/SE/DB/2017 gives 11 cm. The big difference in the overlay thickness between the two methods is caused by differences in seasonal factors, temperature correction factors and formulas in overlay calculation.Keywords: Benkelman Beam, Deflection, Overlay